Peningkatan Hasil Belajar Matematika Materi Satuan Panjang melalui Media Tangga Pintar pada Peserta Didik Kelas III SD - Frederikus Yosafat Balaweling; Maria Angelina Fransiska Mbari; Marianus Yufrinalis (Journal on Education, 2023)
This study aims to improve student learning outcomes by using smart ladder media for third grade students at SD Inpre Wairotang. This research is a classroom action research (CAR) designed to help researchers find solutions in classroom learning. This classroom action research was conducted in two cycles, namely cycle I and cycle II. Of the 28 students, the results showed that after giving action for two cycles, the average value of the test results for improving mathematics learning outcomes in unit length material using smart ladder media increased. Cycle I the first meeting obtained a value of 0% and the second meeting was 3.6% with the category not fulfilling the KKM and in cycle II there was an increase in the first meeting of 14.28% and the second meeting of 100% which also increased by 100%. From these results it shows that, learning to increase learning outcomes in mathematics on unit length material using clever ladder media can be applied to improve student learning outcomes, especially in mathematics subject length unit material.